2013
DOI: 10.1002/2013jd020262
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transport mechanisms of black carbon over East Asia in spring during the A‐FORCE aircraft campaign

Abstract: Mechanisms of vertical transport of black carbon (BC) aerosols and their three‐dimensional transport pathways over East Asia in spring were examined through numerical simulations for the Aerosol Radiative Forcing in East Asia (A‐FORCE) aircraft campaign in March–April 2009 using a modified version of the Community Multiscale Air Quality (CMAQ) modeling system. The simulations reproduced the spatial distributions of mass concentration of BC and its transport efficiency observed by the A‐FORCE campaign reasonabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 98 publications
(170 reference statements)
6
55
0
Order By: Relevance
“…The model generally overestimates BC at 40-45 • N. Another major bias is that there is an overestimate in model simulations at lower altitudes and an underestimate at higher altitudes near 50 • N, mainly because there are large uncertainties in the calculations of vertical transport of BC (Koffi et al, 2012;Oshima et al, 2013). Oshima et al (2013) identified that the uplifting of BC in association with migratory cyclones over northeastern China and the subsequent BC transport by the midlatitude westerlies provided the major pathway for BC export from EA to the free troposphere over the western Pacific during the springtime A-FORCE period. Here the observed high BC concentrations aloft in April may be caused by the same mechanism.…”
Section: -35mentioning
confidence: 98%
See 4 more Smart Citations
“…The model generally overestimates BC at 40-45 • N. Another major bias is that there is an overestimate in model simulations at lower altitudes and an underestimate at higher altitudes near 50 • N, mainly because there are large uncertainties in the calculations of vertical transport of BC (Koffi et al, 2012;Oshima et al, 2013). Oshima et al (2013) identified that the uplifting of BC in association with migratory cyclones over northeastern China and the subsequent BC transport by the midlatitude westerlies provided the major pathway for BC export from EA to the free troposphere over the western Pacific during the springtime A-FORCE period. Here the observed high BC concentrations aloft in April may be caused by the same mechanism.…”
Section: -35mentioning
confidence: 98%
“…Here we use the GEOS-Chem model (version 9-01-03) with a horizontal resolution of 2 • latitude by 2.5 • longitude and 47 vertical layers to simulate BC concentrations for March and April 2010, following six months of spin-up. BC simulations in GEOS-Chem have been evaluated over the United States using surface measurements from the Interagency Monitoring of Protected Visual Environments (IM-PROVE) network (Park et al, 2003) and over the Himalayas and the Tibetan Plateau using wet deposition flux measurements (Kopacz et al, 2011). The simulation of BC in GEOSChem has been discussed by Park et al (2003) and Park et al (2005); here we describe the key features of the BC simulation, as they pertain to this study.…”
Section: Geos-chem Model and Its Adjointmentioning
confidence: 99%
See 3 more Smart Citations